ACADEMIC ATMOSPHERE, PROVISION OF FACILITIES AND ITS EFFECT ON THE SPIRIT OF PERMANENT LECTURERS AT STIE TRISNA NEGARA OKU TIMUR - Winda Feriyana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This research aims to partially and collectively analyze the influence of the academic atmosphere, the provision of facilities on the work spirit of permanent lecturers and to analyze the most dominant variable in influencing the work spirit of permanent lecturers at STIE Trisna Negara OKU Timur. The regression analysis results and the correlation between academic atmosphere and employee work spirit show the regression model Ŷ = 21,908 + 0.551X1 + e with a correlation coefficient of 0.589. The results of the regression analysis and the correlation between the provision of facilities on employee work spirit show the regression model Ŷ = 46.446 + 0.027X2 + e with a correlation coefficient of 0.033. The results of multiple regression analysis and the correlation between the academic atmosphere and the provision of facilities together on work spirit show the regression model Ŷ = 19.792 + 0.553X1 + 0.043X2 + e with a correlation coefficient of 0.592 at the 95% confidence level, it is found that the academic atmosphere and provision facilities can simultaneously predict employee work spirit. From the multiple linear regression equation above, it shows that the academic atmosphere variable (X1) has a more dominant influence on employee work spirit than the provision of facilities. This research was conducted on 45 respondents with the analytical method used is path analysis using SPSS software. Keywords : Academic Atmosphere, Facility Provision, Work spirit